Comparison Of Orthopantomogram and Lateral Cephalogram for Gonial Angle, Mandibular Ramus Height And Body Length - Mobina Fatima Zulfiqar; Kanwal Zulfiqar; Ulfat Bashir; Uzair Luqman; Zarnab Rizwan (Journal of Rawalpindi Medical College)
Objective: This study aims to compare orthopantogram and lateral cephalogram for gonial angle and mandibular linear measurements (ramus height and body length).